(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify the effect of the (D.C.A.A.T.A.) strategy on the achievement of fifth-grade science students in biology. To achieve the research objective, the researcher formulated the following null hypothesis: "There is no statistically significant difference at the (0.05) level between the average scores of students in the experimental group who will study biology according to the (D.C.A.A.T.A.) strategy and the average scores of students in the control group who will study biology using the traditional method on the achievement test." The researcher adopted a partially controlled experimental design for two independent groups, one experimental and the other control, with a post-test for achievement. To achieve the research objective, a random sample of (67) students was selected and distributed between the two research groups. The number of students in the experimental group was (34) students, and the number of students in the control group was (33) students. The equivalence between the students of the two research groups was carried out according to the following variables: (the students’ chronological age calculated in months, the previous information test, the previous achievement in biology, and the Raven Intelligence Test), in the second semester of the academic year (2024-2025). The researcher identified the subject matter that would be taught during the experiment period, which amounted to three chapters from the biology book for the fifth scientific grade, and formulated the behavioral objectives for the topics that would be taught, which were (180) behavioral objectives according to Bloom’s levels (remembering, understanding, application, analysis, synthesis, and evaluation). The researcher prepared (18) teaching plans for each of the two research groups, based on the topics she adopted for teaching during the experimental period. To achieve the research objective, the researcher prepared the research tool, the achievement test, consisting of (40) objective paragraphs with four alternatives. Its validity and reliability were confirmed, and using appropriate statistical methods, the results showed that the experimental group, which studied using the D.C.A.A.T.A. strategy, outperformed the control group, which studied using the traditional method, in the achievement test. Based on the research results, the researcher developed a number of conclusions, recommendations, and proposals, which are mentioned in Chapter Four.